Student-Generated Daily Question Cards for ESP Speaking in Dental Nursing: A Qualitative Case Study - Achmad Basir (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This qualitative case study examined the implementation of Student-Generated Daily Question Cards in an ESP speaking class for dental nursing students at Poltekkes Kemenkes Makassar. The study involved 48 sixth-semester students and one English lecturer, with data gathered through six classroom observation meetings, semi-structured interviews with 25 purposively selected students and the lecturer, and supporting documentation. The data were analyzed thematically using Miles and Huberman’s interactive model. The study was conducted to address the persistent difficulty many health-related EFL learners experience in speaking English meaningfully and to explore a practical, context-based strategy for improving ESP speaking instruction. The findings revealed four major themes: the cards increased classroom interaction and oral participation, supported students’ willingness to speak more freely, fostered learner-centered engagement through student-generated questioning, and strengthened contextualized communication related to dental nursing practice, including patient education, oral hygiene, and clinical routines. Rather than functioning merely as a speaking prompt, the activity helped transform classroom discourse into a more interactive and profession-oriented learning process. The novelty of this study lies in showing how student-generated question cards can combine active learning, learner autonomy, and ESP relevance within instructional format. The study concludes that Student-Generated Daily Question Cards are an effective and practical tool for encouraging meaningful speaking practice in dental nursing education. The main implication is that ESP lecturers can adapt this strategy to promote student-generated, discipline-based oral tasks that connect language practice with future professional communication needs.